2022
DOI: 10.1021/acsaem.2c01085
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy and Composition Engineering of Manganese Hexacyanoferrate for Sodium-Ion Storage

Abstract: Manganese hexacyanoferrate (MnHCF) with an open framework is suitable for accommodating sodium ions. However, it suffers from severe capacity decay caused by the large structural deformation resulting from the Jahn−Teller (J−T) distortion of Mn−N 6 octahedra. By taking advantage of the strong chelation between EDTA and Mn ions, a strategy employing Mn vacancies (V Mn ) in combination with the introduction of Ni is proposed to suppress the J−T distortion of MnHCF. A Ni-doped MnHCF with V Mn and a low crystal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…[12] Furthermore, due to the large grain size, Mn-PBA is not fully activated, achieving a maximum specific capacity of 123 mAh g −1 at the second cycle (Figures S13b, S14, and S15, Supporting Information). [12,36] The rate performance of both samples is compared and shown in Figure 3c and Figure S16 (Supporting Information). MnCuNi-PBA exhibits higher reversible capacities at current densities of 0.01, 0.05, 0.1, 0.2, 0.3, 0.5, 0.8, 1.0, 1.5, and 2.0 A g −1 , with values of 113.1, 106.1, 102.8, 98.4, 95.7, 90.8, 85.2, 81.8, 73.8, and 66.2 mAh g −1 , respectively, which are substantially higher than those of the Mn-PBA.…”
Section: Resultsmentioning
confidence: 99%
“…[12] Furthermore, due to the large grain size, Mn-PBA is not fully activated, achieving a maximum specific capacity of 123 mAh g −1 at the second cycle (Figures S13b, S14, and S15, Supporting Information). [12,36] The rate performance of both samples is compared and shown in Figure 3c and Figure S16 (Supporting Information). MnCuNi-PBA exhibits higher reversible capacities at current densities of 0.01, 0.05, 0.1, 0.2, 0.3, 0.5, 0.8, 1.0, 1.5, and 2.0 A g −1 , with values of 113.1, 106.1, 102.8, 98.4, 95.7, 90.8, 85.2, 81.8, 73.8, and 66.2 mAh g −1 , respectively, which are substantially higher than those of the Mn-PBA.…”
Section: Resultsmentioning
confidence: 99%
“…After that, He and coworkers reported that the phase structure of Mn-HCF would change from rhombohedral to cubic after Sn 4+ doping, and enhanced capacity retention after 100 cycles at 240 mA g –1 was obtained (80.5% vs 54.0% for bare Mn-HCF) . Lately, Jahn–Teller distortion was found by Shao’ group to be repressed through employing Mn vacancies (V Mn ) in combination with Ni doping …”
Section: Prussian Blue Cathodesmentioning
confidence: 99%
“…162 Lately, Jahn−Teller distortion was found by Shao' group to be repressed through employing Mn vacancies (V Mn ) in combination with Ni doping. 163 In order to further enhance the electrochemical performance, multication lattice substitution has been employed. 164,165 High quality (HQ)-Ni x Co 1−x [Fe(CN) 6 ] PBAs were synthesized through a chelating agent (trisodium citrate)/surfactant (polyvinylpyrrolidone, PVP) coassisted crystallization method with fewer [Fe(CN) 6 ] vacancies and water molecules in Han's group.…”
Section: Compositing With Conductive Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the relevant literature, the differences in the electrochemical performances of these materials are mainly caused by two aspects: (1) A large number of Fe(CN) 6 vacancy defects. These defects will be occupied by some coordination water, leading to an increase in the lattice water content and blockage of Na + transport channels [21,[27][28][29][30]. At the same time, the presence of excessive defect sites and coordination water leads to the collapse of the cyanide connection framework during the cycling process, further affecting the storage performance of sodium ions.…”
Section: Effect Of Fe-mn Ratio On Properties Of Mnhcfmentioning
confidence: 99%